STUDENT’S GAMING EXPERIENCE IN MASTERING VOCABULARY - Luqman Fariz; Maman Suryaman (PROJECT (Professional Journal of English Education), 2021)
Technological advances provide vast opportunities for second language learners to access various materials and methods to learn languages. In Indonesia, the 4.0 revolution creates numerous opportunities for educational innovation, especially in learning English as a foreign language (EFL). This study aims to reveal how a student's gaming experience can help him in mastering English vocabulary. The study used a Narrative Inquiry design to explore student's experience in playing video games that provide an alternative way of acquiring English vocabulary. Semi-structured interviews were used to explore student's learning experiences. Based on the thematic analysis, qualitative data showed that the student's learning experience has several positive impacts on the student's vocabulary acquisition. In addition, this study also revealed that the Role-Playing Game (RPG) and Story Rich genres greatly influenced the student's vocabulary acquisition. Keywords:  Gaming Experience, Vocabulary Mastery, EFL Student, Narrative Inquiry